Analisis Miskonsepsi Siswa SD pada Materi Gaya dan Gerak - Rizki Halimah Nasution; Tommy Tanu Wijaya; M. Jaya Adi Putra; Neni Hermita (Journal of Natural Science and Integration, 2021)
This research is to find out and describe elementary students misconception on the concept of force and motion. Data collection methods using tests in the form of four tier tests and interviews. Sampling techniques through saturated sampling is applied to obtain students who will be examined throughbout the fifth grade of SDN 147 Pekanbaru. The research data were analyzed using descriptive quantitative analysis. The results showed that elementary students misconceptions could be categorized as “medium” with an average of 54,29% or totaling 76 students from 140 students studied. The bighest misconception on the concept spring force with a misconception of 75% or a total of 105 students from 140 students studied. The lowest misconception on the concept of the influence of force on the motion of objects with a misconception of 19,29% or a total of  27 students from 140 students studied. Comparison of the percentage of misconceptions of male and female students on the concepts of force and motion included in “medium category”, with an average percentage of misconceptions that occur in male students by 51,56%  and female students by 51,31%. The factors causing the occurrence of misconceptions in students come from students, the context and teaching methods.Keywords: misconceptions, the force and motion, elementary studentsABSTRAK Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan miskonsepsi siswa sekolah dasar pada materi gaya dan gerak. Metode pegumpulan data menggunakan tes berupa four tiet test dan wawancara.  Teknik pengambilan sampel melalui sampling jenuh yaitu seluruh siswa kelas V SDN 147 Pekanbaru. Data hasil penelitian dianalisis menggunakan analisis kuantitatif deskriptif. Hasil penelitian menunjukkan bahwa miskonsepsi yang terjadi pada siswa sekolah dasar termasuk dalam kategori miskonsepsi “sedang” dengan rata-rata 54,29% atau berjumlah 76 siswa dari 140 siswa. Miskonsepsi tertinggi pada sub indikator terkait gaya pegas dengan miskonsepsi sebesar 75% atau berjumlah 105 siswa dari 140 siswa. Miskonsepsi terendah pada sub indikator pengaruh gaya pada gerak benda dengan persentase miskonsepsi sebesar 19,29% atau berjumlah 27 siswa dari 140 siswa. Perbandingan persentase miskonsepsi siswa laki-laki dan perempuan pada materi gaya dan gerak termasuk dalam kategori “sedang” dengan rata-rata miskonsepsi yang terjadi pada siswa laki-laki sebesar 51,56% dan perempuan sebesar 51,31%.  Faktor penyebab terjadinya miskonsepsi pada siswa berasal dari peserta didik, konteks dan metode mengajar. Kata kunci: miskonsepsi, gaya dan gerak, siswa sekolah dasar